Chemogenetic ablation of dopaminergic neurons leads to transient locomotor impairments in zebrafish larvae. (3rd August 2015) - Godoy, Rafael; Noble, Sandra; Yoon, Kevin; Anisman, Hymie; Ekker, Marc
Abstract To determine the impact of a controlled loss of dopaminergic neurons on locomotor function, we generated transgenic zebrafish, Tg(dat:CFP‐NTR), expressing a cyan fluorescent protein‐nitroreductase fusion protein (CFP‐NTR) under the control of dopamine transporter (dat) cis‐regulatory elements. Embryonic and larval zebrafish express the transgene in several groups of dopaminergic neurons, notably in the olfactory bulb, telencephalon, diencephalon and caudal hypothalamus. Administration of the pro‐drug metronidazole (Mtz) resulted in activation of caspase 3 in CFP‐positive neurons and in a reduction in dat‐positive cells by 5 days post‐fertilization (dpf). Loss of neurons coincided with impairments in global locomotor parameters such as swimming distance, percentage of time spent moving, as well as changes in tail bend parameters such as time to maximal bend and angular velocity. Dopamine levels were transiently decreased following Mtz administration. Recovery of some of the locomotor parameters was observed by 7 dpf. However, the total numbers of dat‐expressing neurons were still decreased at 7, 12, or 14 dpf, even though there was evidence for production of new dat‐expressing cells. Tg(dat:CFP‐NTR) zebrafish provide a model to correlate altered dopaminergic neuron numbers with locomotor function and to investigate factors influencing regeneration of dopaminergic neurons. <boxed-text content-type="graphic" id="jnc13214-blkfxd-0101" position="anchor" orientation="portrait"> </boxed-text> We have generated transgenic zebrafish expressing nitroreductase for the conditional and specific ablation of dopaminergic (DA) neurons in the larval zebrafish brain. We are able to induce a persistent reduction in DA neurons with transient locomotor impairments. Our transgenic zebrafish offer a model for understanding the impact of altered DA neuron populations on larval locomotor function and for the study of dopamine neuron regeneration following tissue specific ablation.